Impact of spontaneous liposome modification with phospholipid polymer-lipid conjugates on protein interactions. Issue 1 (31st December 2022) - Suzuki, Haruna; Adler, Anna; Huang, Tianwei; Kuramochi, Akiko; Ohba, Yoshiro; Sato, Yuya; Nakamura, Naoko; Manivel, Vivek Anand; Ekdahl, Kristina N; Nilsson, Bo; Ishihara, Kazuhiko; Teramura, Yuji
ABSTRACT: Liposome surface coating has been studied to avoid the immunological responses caused by the complement system, and alternative materials to poly(ethylene glycol) (PEG) have been explored recently since the production of anti-PEG IgM antibodies has been found in humans. We previously reported a liposome coating with poly(2-methacryloyloxyethyl phosphorylcholine) (poly(MPC))-conjugated lipids (PMPC-lipids) and demonstrated its protective effect on blood protein interactions. Here, we attempted to modify the liposome surface by exogenously adding PMPC-lipids, which were spontaneously incorporated into the outer membrane via hydrophobic interactions. The polymerization degree of the PMPC segment was regulated from 10 to 100. The incorporated ratio of PMPC-lipid increased with a decrease in the degree of PMPC polymerization. Due to surface modification with PMPC-lipids, increase in the length of the PMPC-chain increased the size of the liposomes. The modified liposomes were kept stable for 14 d in terms of their size, polydispersity, and surface properties, where approximately 70% of PMPC-lipids were incorporated into the liposome surface. We demonstrated that liposome surface modification with PMPC-lipids can inhibit protein adsorption when exposed to serum, regardless of the degree of polymerization of PMPC. In addition, the PMPC-lipid modified surface was not recognized by the anti-PEG IgM antibody, whereas PEG-lipid was recognized by the antibody. Thus, we successfully fabricated an inert liposome surface via spontaneous modification with PMPC-lipids, where only the outer bilayer surface was modified. This technique can be available for full loading of water-soluble active pharmaceutical ingredient inside the modified liposome. GRAPHICAL ABSTRACT: uf0001